Table of Content - -, (Journal of Arabic Language Sciences and Literature, 2025)
Table of Content:1. Verbal Antithesis in the Holy Quran: A Rhetorical, Statistical and Analytical StudyDr. Ahmed Mohammed Al-Farsi2. Islam's view of scienceMs. Amani Saud Khaishan Al-Qurashi3. The protagonist's image in Palestinian novels after Oslo accords in light of critical discourse analysis: A reading of "when the volves grow old and velvet"Mr. Khalil Mahmoud Harb ,  Co-Prof. Musa Mitri Khoury4. Functions of the Tropes in Jassim Al-Sahhih’s poetryMs. Amani Ahmad Mohammad Alhajjaji5. American Interconnected Text Theory:  A Critical View of Western ReceptionProf. Brahim Amri Mohamed6. Manifestations of rhetorical condensation and its semantic impact in free poetry (Fadwa Touqan) as a model Poem (To the martyr Wael Zaatir)Dr. Abdullah Mohmmed Hommod Al-Tobi , Dr. Mahmood Saed Safe Al-Drmaki
Keywords: Journal of Arabic Language and Literature